Design And Development Of 200 Watts Bidirectional Cllc Resonant Converter For Uninterruptible Power Supply Applications - Abdullah, Muhammad Faizal (2019)
Uninterruptible power supply (UPS) is widely employed to provide reliable power in many critical applications such as computers, data centers, surgical rooms, and telecommunication equipment. UPS system essentially consists of a battery charger, battery, and inverter. Conventionally, two unidirectional converters (battery charger and inverter) are often implemented separately where each of the converters will process the power in one direction. However, in certain applications, this configuration is not optimal, hence, a bidirectional converter is the solution. In UPS, a bidirectional converter configuration leads to a reduction in hardware components because battery charger and inverter can be built in one converter unit. In this dissertation, a detailed design and implementation of bidirectional CLLC resonant converter and new high efficient inverter for UPS system that provide bilateral power flow are presented. In the proposed topologies, a two-stage inverter is implemented where it consists of a front-end converter namely bidirectional CLLC resonant converter. The first topology consists of hybrid pulse width modulation (HPWM) inverter combined with the resonant converter and named as UPS 1. The second topology consists of highly efficient sine-wave inverter combined with the resonant converter and named as UPS 2. These topologies offer several advantages such as excellent soft switching performance, buck/boost operation capability, and simple switching control. The simulation and experimental results of 200 W prototypes are presented for comparison, analysis, and validation. The presented results show that the CLLC resonant converter achieves zero voltage switching (ZVS) for active switches xxi and zero current switching (ZCS) for rectifier diodes, while the inverters show good quality output waveforms with high overall efficiency. The efficiency performance shows that the proposed UPSes were able to produce high efficiency in both forward and backward modes. For UPS 1, the peak efficiency was 88.08 % in forward mode and 92.24 % in backward mode. For UPS 2, the peak efficiency was 90.71 % in forward mode and 91.82 % in backward mode. When in forward mode, the efficiency of UPS 2 was slightly higher than the efficiency of UPS 1, but in backward mode, the efficiency of UPS 1 was slightly better than the efficiency of UPS 2